Study on Seismic Performance of Recycled Steel Fibers Locally Reinforced Cruciform Concrete Frame Beam-Column Joint - Yan Li; Rong-Hua Zhao; Dong-Yi Li; Chang Qu (Advances in Civil Engineering)
At present, concrete frame structures are widely used, and the frame beam-column joints are the key parts of the whole frame in seismic resistance. In previous studies, recycled steel fiber-reinforced concrete is a new type of environment-friendly reinforcement material, which can also be widely used in the construction industry. Therefore, in this paper, MTS electrohydraulic servo loading systems were used to carry out low-cycle reciprocating cyclic loading tests to study the seismic performance of five 1/2 scale cruciform concrete frame beam-column joint specimens with plain concrete, normal steel fiber-reinforced concrete, and three recycled steel fiber-reinforced concrete with different fiber contents in the joint core area. The results show that the addition of normal steel fibers can improve the bearing capacity, ductility, energy dissipation capacity, and shear strength of concrete frame joint specimens and delay the stiffness degradation of joint specimens, recycled steel fibers can improve the seismic performance of the cruciform concrete frame joints better than normal steel fibers, and the seismic performance increases gradually with the increases of volume ratio of recycled steel fibers. Moreover, with the recycled steel fiber content from 0.5% to 1.0% and then to 1.5%, the increased amplitude of the seismic performance of joint specimens increases. Considering the reinforcing effect of recycled steel fibers on concrete matrix and based on the design formula of shear capacity of reinforced concrete joints, the design formulas of shear capacity of recycled steel fiber-reinforced concrete beam-column joints were established by using the statistical analysis method and the baroclinic rod-truss model, and the calculation results were in good agreement with the test results. This study can provide references for seismic performance research of steel fiber-reinforced beam-column joints and the recycling of steel wire from waste tires.